Comparative Study of Efficacy and Safety of Ayurveda and Allopathic Treatments for Amlapitta (Hyperacidity): A Systematic Literature Review - Gunarathne, B.N.N.K.; Kulanatha, I.G.P.R. (Faculty of Indigenous Medicine, University of Colombo, 2025)
Hyperacidity, known as Amlapitta in Ayurveda, is a prevalent gastrointestinal disorder characterized by excessive gastric acid secretion. Both Ayurveda and Allopathic treatments offer therapeutic benefits, yet a systematic evaluation of their efficacy and safety is needed. This study aims to compare the outcomes of these two approaches. A systematic literature review (SLR) was conducted per PRISMA guidelines using PubMed, ResearchGate, and Google Scholar to identify studies published between 2014 and 2024. The review focused on Amlapitta related studies, using a PRISMA flow chart for selection. From 77 articles, 12 observational studies met the inclusion criteria and were analyzed for the efficacy and safety of Ayurvedic and Allopathic treatments, emphasizing therapeutic outcomes and side effects. Allopathic treatments like Omeprazole-Amoxicillin and Ilaprazole showed high short-term efficacy, with success rates of 97.73% and 89%, respectively, for symptom relief and H. pylori eradication. However, Nizatidine showed lower efficacy (49.2%). Ayurvedic formulations demonstrated comparable effectiveness: Avipattikarachurna achieved 100% relief in Klama and 75% in Hrit-kanta daha, while Drakshadyaghrita showed 84.66% efficacy in reducing key symptoms. Allopathic drugs effectively suppressed gastric acid and eradicated Helicobacter pylori, but their prolonged use was linked to side effects like nausea, headache, gastrointestinal issues and long-term risks such as vitamin deficiencies and gut microbiota imbalance. Conversely, Ayurvedic remedies like Avipattikara churna, Patoladi kwatha, and Draksadya ghrita offered a holistic approach with fewer, milder side effects and no known long-term risks.
Keywords: Amlapitta; Safety; Side effects; Treatments; Hyperacidity